PERENCANAAN DAN PENGENDALIAN KETERSEDIAAN SPARE PART MOBIL DI BENGKEL JOSUA - Nainggolan, Van Becham; Welly Sugianto (Computer Science and Industrial Engineering, 2024)
This study aims to plan and control the inventory of car spare parts at Josua Auto Repair Shop in Tanjung Piayu, Batam City, addressing issues like frequent out-of-stock items, hazardous mechanic positions, disorganized layout, and inadequate tools. The Economic Order Quantity (EOQ) method is used to forecast sales and determine optimal ordering frequency and costs for key spare parts such as engine oil, oil filters, brake pads, brake fluid, and spark plugs. Results show that for engine oil, the sales forecast from May 2023 to April 2024 is 1000 pcs with a purchasing frequency of 13 times per year and an optimal order of 75 pcs per purchase, with storage costs of IDR 153,000 and ordering costs of IDR 431,000. Oil filters are projected to sell 1000 pcs with a frequency of 16 times per year and an optimal order of 61 pcs, with storage costs of IDR 111,000 and ordering costs of IDR 205,000. Brake pads, brake fluid, and spark plugs are similarly analyzed. This study provides guidance for Josua Auto Repair Shop in effectively managing inventory, reducing stock shortages, and improving customer service.